Evaluation of Aesthetic and Quality-of-Life Results after Immediate Breast Reconstruction with Definitive Form-Stable Anatomical Implants. Issue 2 (February 2016) - Kuroda, Flavia; Urban, Cicero; Zucca-Matthes, Gustavo; de Oliveira, Vilmar Marques; Arana, Gabriel Hubner; Iera, Marco; Rietjens, Mario; Santos, Gabriela; Spagnol, Caroline; de Lima, Rubens Silveira
Abstract : Background: Although there are many reports on different techniques in breast reconstruction, there are few data regarding immediate breast reconstruction with definitive form-stable anatomical implants in terms of aesthetics and quality-of-life outcomes. Methods: Ninety-four patients underwent mastectomy with immediate breast reconstruction using anatomical implants and contralateral symmetrization. Aesthetic results were evaluated by three different methods: the patient's self-report, the assessment of four independent specialists (two breast surgeons and two plastic surgeons from different institutions), and the BCCT.core software. Quality of life was evaluated by means of the BREAST-Q instrument. Results: Average age ± SD was 52.1 ± 11.6 years. Most of patients had medium size breasts and T1 tumors. Patients had evaluated their aesthetic results better than did software and specialists. There was no significant difference in the comparison between software and specialist's evaluation. Multifactorial analysis showed that age older than 70 years and radiotherapy were significant risk factors for poor aesthetic outcomes after immediate breast reconstruction with implants. Considering quality of life, most of the patients were satisfied with their outcome and psychosocial and sexual well-being. Conclusion: Immediate breast reconstruction with implants and contralateral symmetrization had a positive impact on the quality of life and showed satisfactory outcomes when evaluated by subjective and objective methods.